Thermally deposited silver-doped cuprous oxide solar cell on textured silicon and its devices modelling - Tuama, Alaa Nihad (2022)
Thin films of metal oxide semiconductors/conducting nanoparticles (NPs), for example, Cuprous oxide (Cu2O): silver thin films may be modified via different treatments in fabricating desired materials including an active layer for solar cell applications. Furthermore, the modified pure Cu2O thin films were successfully prepared via the thermal evaporation method and doped with small various doping ratios of Ag NPs (0.01, 0.02, 0.03, 0.04, 0.05,0.06, and 0.07) wt.% on silicon and glass substrates. Furthermore, pure and Ag-doped Cu2O thin films were employed to fabricate Cu2O:Ag/n-Si and Cu2O:Ag/etched-n-Si solar cells. Therefore, the morphology, structural, electrical, optical, as well as solar cell efficiency properties were examined. The phase structure of Cu2O:Ag thin films determined by XRD show the four main peaks’ existence at 2θ = (30°, 37°, 43°, 62), which corresponds to the {(110), (111), (200), (220)} respectively with crystallite size between 3-22.5 nm indicating the growth of the films with quantum dot structure. FESEM analysis of Cu2O:Ag thin films show that the nanoparticles did not accumulate on the surface and homogeneously separate on the substrates' surface. The AFM analysis of the films indicated a smooth and homogeneous surface morphology. It is composed of small grains, which indicate the interaction of Ag-NPs with Cu2O atoms. The optical properties are influenced by the Ag doping, the films’ thickness, and the quantization effect that increases the prepared films' energy bandgap. The solar cell performance and efficiency evaluation was performed using I-V characteristic curves under dark and illumination for Cu2O:Ag/n-Si as well as Cu2O:Ag/etched-n-Si. Apart from that, it was observed that the efficiency with respect to the solar cells significantly raised to 4.82% as well as 6.48%, respectively. This work's efficiency enhancement can be ascribed to the modified properties with respect to Cu2O thin films due to homogeneity achieved by controlling the deposition process, small thickness, and the high surface area created by the small particle size and laser etching process.